Efektivitas Beauveria bassiana vuill. dengan Berbagai Media Pembiakan Massal untuk Mengendalikan Wereng Coklat (Nilaparvata lugens stal.) - Rosita Rosita; Samharinto Soedijo; Noor Aidawati (www.ulm.ac.id, 2022)
Oryza sativa L. can be called an important commodity because it is used as a staple food. Farmers in cultivating rice expect high yields, but there are obstacles that cause yields to decline, namely the attack of the Brown Stem Planthopper (BSP) (Nilaparvata lugens Stal.) which can lead to crop failure. Farmers controlling N. lugens still use insecticides. Control by using insecticides is known to have a negative impact on users and the environment and can cause resistance, resurgence and residue. One of the safe controls is the use of Beauveria bassiana as an entomopathogenic fungus. This study was conducted to determine the effectiveness of B. bassiana cultured on various media in controlling WBC attacks. The design used was a Completely Randomized Design (CRD) with 6 treatments, namely control treatment without B. bassiana, control with B. bassiana grown on PDA media, B. bassiana grown on corn media, and B. bassiana growing on media. grown on rice media, given B. bassiana grown on bran media, given B. bassiana grown on husk ash and repeated 4 times. Observations were made after one application by observing mortality (mortality) every 24 hours for 7 days. The results of the observation that the highest mortality percentage was found in the corn media treatment reaching 47.50%, rice media 40%, bran media 18.75% while the lowest was found in the husk media, namely 15%.